A26 TREATMENT OUTCOMES OF HCV-INFECTED PATIENS IDENTIFIED THROUGH THE COMMUNITY POP-UP CLINIC. (1st March 2018) - Kiani, G; Shahi, R; Raycraft, T; Alimohammadi, A; Singh, A; Conway, B
Abstract: Background: In Canada, it is estimated that over 300, 000 individuals are infected with HCV, with 60, 000 residing in British Columbia. The prevalence of infection on Vancouver's Downtown East Side (DTES) may exceed 70%, with relatively few individuals having been treated to date. This may relate to a lack of engagement in medical care. We developed a novel model of intervention, the Community Pop-up Clinics (CPC) as a tool to enhance access to medical care and HCV therapy in this vulnerable population. Aims: We aim to further understand the treatment outcomes of HCV infected individuals identified through this initiative. Methods: Participants were recruited at CPCs held at several community centres. OraQuick® HCV Rapid Antibody and HIV Rapid Antibody point-of-care testing was offered. Participants identified as HCV positive were provided the opportunity to engage in care at a multidisciplinary clinic. A questionnaire was administered to collect demographic information, HCV disease knowledge, and data regarding barriers to receiving healthcare. A $10 gift-card incentive was provided for participants who completed the demographic questionnaire and testing. Results: A total of 2378 participants (mean age 49.9 years, 93.4% male) were tested for HCV infection, with 658 (27.7%) infected with HCV including 51 (7.7%) co-infected with HIV. Among HCV infected participants, 157 (27.6%) were linked to care (76% male, 30% First Nations, 28% homeless, 78% recent PWID), 26 (16.9%) started treatment for HCV infection, 19 (73%) completed treatment, and 16 (84.2%) achieved sustained virologic response (SVR). Groups under-represented among those engaged in care include: females (7%), lack of knowledge about how to access health care (9%), homeless (9%), perceived their health status as good (14%), First Nations (15%). Conclusions: Our CPC approach in a neighborhood with HCV prevalence of 70% has successfully identified over 600 HCV-infected individuals and engaged a significant proportion of them in care. Additional efforts must be undertaken to engage certain populations such as women, First Nations and those who are homeless and in ensuring that engagement leads to enhanced access to curative HCV therapies in all eligible patients. Funding Agencies: None